HOME HAZARD REMOVAL TO REDUCE THE RATE OF FALLS AMONG COMMUNITY DWELLING OLDER ADULTS: A RANDOMIZED CLINICAL TRIAL. (16th November 2018) - Stark, S; Keglovits, M; Somerville, E; Hu, Y
Abstract: Falls are the leading preventable cause of morbidity, mortality, and premature institutionalization for community-dwelling older adults. A hybrid effectiveness/implementation trial assigned 310 older adults receiving services from community agencies in urban St. Louis, Missouri, to a home hazard removal intervention delivered over 2 weeks with a 6-month booster, or usual care control. Eligible participants did not have dementia and were aged 65 years or older, were at high risk for falling, and resided in the community. The intervention (n=141) was a home hazard removal program delivered by an occupational therapist in the home that included a comprehensive clinical assessment of the individual, an environmental assessment, and implementation of a tailored hazard removal plan. The intervention was delivered in two or three sessions and included an additional booster session at 6 months. The primary outcome was the number of falls over 12 months. Participants were predominantly African American (56%). At baseline, the mean (SD) age was 75 (7.4) years; 79% were female. At 12 months, the mean (SD) number of falls was 1.5 (3.5) in the intervention group and 2.3 (6.6) in the control group. There was a 38% reduction in the risk of falling (P=0.027) in the intervention group. A brief home hazard removal program significantly reduced the rate of falls among community-dwelling older adults at high risk for falling.